Environmental, social and governance (ESG) performance and retail investor demand for IPOs - Chong, Kez Sing (2021)
The trend of environmental, social and governance (ESG) investing has been rising in prominence around the globe, previous findings found that retail investors have been increasing demand for sustainable investment too. On the other hand, Initial Public Offerings (IPOs) is an important juncture to the development of the business that enables the business to gain public exposure where the retail investor demand for IPOs is also the key to the success of IPOs.